Maltodextrin Consumption Impairs the Intestinal Mucus Barrier and Accelerates Colitis Through Direct Actions on the Epithelium - Zangara, Megan T.; Ponti, András K.; Miller, Noah D.; Engelhart, Morgan J.; Ahern, Philip P.; Sangwan, Naseer; McDonald, Christine (Frontiers in Immunology, 2022)
Food additives are common components of processed foods consumed in a Western diet. In inflammatory bowel disease patients, some diets that exclude food additives improved clinical disease parameters, suggesting a link between food additives and disease pathogenesis. Food additives also enhanced disease severity in mouse colitis models through incompletely described mechanisms. This study examined the mechanisms by which the food additive maltodextrin (MDX) alters the development of colitis in a murine model. Interleukin-10 knockout (IL10KO) mice were fed diets supplemented with MDX or carboxymethyl cellulose (CMC) to determine the impact on colitis onset and severity; microbiome composition, function, and location; colonic immune cell infiltrates; and mucus layer integrity. Primary IL10KO colonic epithelial monolayers were used to dissect the impact of MDX directly on epithelial differentiation and mucus production. MDX or CMC consumption increased the incidence and severity of colitis, as well as decreased microbiome diversity, altered microbial composition, and decreased fecal acetic acid levels. The number of mucus producing cells were decreased in food additive fed mice and resulted in increased microbial proximity to the intestinal epithelium. In primary intestinal epithelial-derived monolayers devoid of microbes and immune cells, MDX exposure decreased goblet cell number and mucus production in association with downregulated expression of the transcription factor Klf4, a marker of terminally differentiated goblet cells. Additionally, MDX supplementation resulted in crypt hyperplasia and an expanded the Hopx+ injury renewal stem cell niche in a process that required microbial signals in addition to MDX exposure. MDX disrupts the balance of epithelial cell differentiation and proliferation to contribute to disease pathogenesis through direct and indirect actions on the intestinal epithelial barrier.